Вплив імунобіологічного статусу організму телят на продуктивне довголіття - Милостивий, Роман Васильович; Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman (Дніпровський ДАЕУ, 2018)
Отримано результати, що підтверджують існування зв’язку між показниками неспецифічної резистентності організму телят та майбутньої продуктивності корів. Виявлено достовірний позитивний зв’язок між бактерицидною активністю сироватки крові телят та довічним надоєм, виходом молочного жиру та білка (r = 0,63–0,69; P <0,05). Менш тісною була кореляція між продуктивними якостями та лізоцимною активністю сироватки крові (r = 0,57–0,59, P <0,05), а також умістом Ig G і Ig М (r = 0,58–0,63; P <0,05). Водночас зв’язок між показниками довічної продуктивності та фагоцитарної активності нейтрофілів виявився позитивним (r = 0,31–0,41), однак був недостовірним. Здобуті дані свідчать про можливість використання імунобіологічних показників крові телят як маркери майбутньої продуктивності корів. Decrease in productive longevity of highly productive cows in conditions of industrial dairy complexes causes one more problem which is connected with difficulties of herd timely restoration through its own offspring. Therefore, raising of heifers is very important in both breeding and economic importance in dairy cattle breeding. To that extent, significant attention is paid to the researchers' early prediction of the cows future milk productivity, even during their postnatal development. Quite often, the subject of such studies is the state of calves growth and development, while insufficient attention is given to animals blood indicators. In the available literature to us, practically there is no information on the relationship between the values of humoral and cellular immunity of calves with their future milk performance. These blood indicators are traditionally used to characterize body's immunobiological reactivity and the health of calves, and extremely rare to predict their future lifelong milk productivity. This is partly due to the difficulties associated with the duration of such studies, since the cow must complete its productive life. Our studies are covering a considerable period of time (more than ten years). Achieved results demonstrated the possibility of using immunobiological indicators of calves' blood as markers of the cows future productivity. A reliable positive relationship between bactericidal activity of blood serum of three months aged calves and their lifelong milk productivity, milk fat yield and protein (r = 0,63‒0,69, P <0.05) was found. The correlation between productive qualities and lysozyme activity of blood serum were less dense (r = 0,57–0,59; P < 0,05), as well as IgG and IgM (r = 0,58–0,63; P < 0,05). At the same time, the relationship between values of lifelong milk productivity and the phagocytic activity of neutrophils was positive (r = 0,31–0,41), but it was unreliable. Regression analysis has showed that values of productive longevity of Holstein cows at 21–47 % were due to the immunobiological status of the calves' organism in early postnatal ontogenesis. The search for reliable markers for predicting the productive longevity of highly productive cows in early rearing periods is extremely important for making managerial decisions. The experimental data obtained by us are only preliminary and require confirmation at a larger number of animals.
Influence of the immunobiological status of the calves' organism on productive longevity
Keywords: телята; calves; корова; cow; голштинська порода; Holstein breed; показники крові; blood values; довічний удій; lifelong milk productivity